Analisis Yuridis Penentuan Jenis Dakwaan Yang Disangkakan Kepada Terdakwa Dalam Perkara Tindak Pidana Narkotika - Boyman Berkat Humendru; Devi Anggara br Ginting; Rico Natanael Sitorus (Mahesa Research Center, 2020)
This article is aimed to find out the legal basis of the public prosecutor in determining the type of indictment of a narcotics offender. The basis for making the indictment is regulated in KUHP article 143 paragraph (2) and the circular of the attorney general no. 009/19/11/1993. Seeing the narcotics abuse in Indonesia is always increasing in all circles nowadays. S there needs to be a real punishment for uses and dealers. In the prosecution process, a defendant in a narvotics crime will be charged with an alternative indictment. Alternative indictments are composed of several criminal offences which exclude one another from the other.